Revisiting Preclinical Observations of Several Histamine H3 Receptor Antagonists/Inverse Agonists in Cognitive Impairment, Anxiety, Depression, and Sleep–Wake Cycle Disorder - Alhusaini, Mera; Eissa, Nermin; Saad, Ali K.; Beiram, Rami; Sadek, Bassem (Frontiers in Pharmacology, 2022)
A relationship appears to exist between neurotransmitters and various brain disorders. Brain monoamines as serotonin, dopamine, norepinephrine, and histamine, play crucial role in emotions, cognition, pathophysiology, and treatment of several mental disorders. Specific neurological symptoms are associated with dysregulation of such neurotransmitters, leading to many neuropsychiatric brain disorders. The possible involvement of histamine in neuropathology has gained attention recently and, its role in many physiological brain functions including memory, cognition, and sleep wake cycle paved the way for further research, studying the aetiology of several brain disorders. H3 receptor (H3R) evidenced in the brain rodent and human is of special interest, given its unique position as a presynaptic receptor, hence, controlling the synthesis and release of histamine as well as other neurotransmitters in different brain regions. Numerous H3R antagonists/inverse agonists showed great potentials in modulating memory and cognition, mood, and sleep- wake cycle thus, suggesting its potential role in many disabling neurological, major neurocognitive and neurodegenerative diseases such as Alzheimer’s disease, Parkinson’s disease, epilepsy, narcolepsy and major depression. In this review, application of the H3R antagonists/inverse agonists and their pharmacological effects are discussed. Hereby, presenting the utilization and therapeutic potential of histamine ligands in enhancing key manifestations of the neurological disorders, including cognitive impairment, anxiety, depression, and sleep wake cycle dysregulations. Collectively, the current review highlights the behavioural impact of developments of H3R antagonists/inverse agonists, aiming to encourage clinicians and researchers to profile its potential therapeutic role.